CULTURAL HERITAGE OF GREAT SILK ROAD IN TURKESTAN REGION - А. Yu. Baltabayeva; R. Zh. Yesbalayeva; M. B. Shaikhystamova; Naciye Yildiz (Scientific Journal of Pedagogy and Economics, 2019)
The article deals with the development of cultural heritage of Great Silk Road from the literary, cultural, historical and economic point of view in Turkestan region. The leader of Kazakhstan N.A. Nazarbayev in his article “Seven facets of Great Steppe”, points to the Great Silk Road business and emphasizes its value in global development. Since Great Silk Road is not just measured today, the location of the Turkestan city along the Great Silk Road, which was the beginning of civilizations in the Turkestan region, and the historical monuments in Sauran, Turkestan, Sidaq, Karaspan, Zhuantobe, Kultobe and Burzhar were not only the world trade places, but also centres of books, handicrafts, literature. The contribution of this sacrel lands to the development of culture is historically analyzed.